Common Fixed Point Theorem in Complex Valued $b$-Metric Space for Rational Contractions - Dubey, Anil Kumar; Tripathi, Manjula (Journal of Informatics and Mathematical Sciences, 2015)
In this paper we prove the common xed point theorem in complex valued b-metric space for rational contractions. Our results extend, generalize and improve the corresponding result of Uthayakumar and Prabakar [12].